Transaction Costs in Digital Coordinates - S. S. Galazova (Статистика и экономика)
The article examines the problems of studying transaction costs through the prism of the concept of an “extended enterprise” in the digital economy, defines evolutionary approaches to the study of transaction costs, classifies the classification features of transaction costs, the structure and methods of accounting for transaction costs, and also proposes a model of the relationship between transaction and transformation costs in analog and digital economies, which allows a more comprehensive consideration of changes in t transaction costs in digital coordinates.